ANALISIS TINGKAT KESEJAHTERAAN MASYARAKAT NELAYAN DI PANGKALAN PENDARATAN IKAN DESA TANJUNG LUAR, KABUPATEN LOMBOK TIMUR - Mulyani, Laily Fitriani; Asri, Yuliana; Dwiyanti, Septiana (Program Studi Budidaya Perairan Universitas Mataram, 2023)
This service aims to determine the level of welfare of fishing communities in East Lombok. This service was carried out for fishermen at the Tanjung Luar Fish Landing Base, East Lombok Regency, West Nusa Tenggara. The sample in this study is 15% of the total fisherman population in the base area. Data collection technique used is interview. The data analysis technique used was descriptive qualitative analysis. The results showed that the welfare level of the fishing community was 52 respondents (54.1%) belonging to the poor, 36 respondents (37.5%) belonging to the prosperous I, and 8 respondents (8.3%) belonging to the prosperous II. If it is related to the 2022 East Lombok Regency Minimum Wage, which is Rp. 2,372,532, then all respondents fall into the poor category, the income of the pre-prosperous people is Rp. 897,000, the prosperous people I Rp. 1,149,000, and the prosperous people II Rp. 1,470,000.